Evaluation and Theoretical Study on the Anti-inflammatory Mechanism of 1-Nitro-2-phenylethane - Vale, Joyce K. L.; Lima, Anderson B.; Pinheiro, Bruno G.; Cardoso, Alessandra S.; Silva, Joyce K. R.; Maia, José G. S.; de Sousa, Gloria E. P.; da Silva, Albérico B. F.; Sousa, Pergentino J. C.; Borges, Rosivaldo S. (Planta Medica, 2013)
In this study, 1-nitro-2-phenylethane was evaluated with respect to its effects in edema models of acute inflammation induced with carrageenan, dextran, and croton oil. 1-Nitro-2-phenylethane produced inhibition of rat paw edema induced by carrageenan and dextran at the doses of 25 and 50 mg/kg. The same doses caused an inhibition of croton oil-induced ear edema in mice. Our results suggest that 1-nitro-2-phenylethane has anti-inflammatory activity, probably of peripheral origin, acting in the synthesis and/or release of inflammatory mediators. A conformational study of 1-nitro-2-phenylethane was carried out using density functional theory calculations, showing three different groups of conformers corresponding to energy minimum geometries. The stereoelectronic repulsions are responsible for conformational preferences and the one most stable conformer. The prostaglandin endoperoxide synthase mechanism is related more to electrophilic than nucleophilic properties.
Keywords: anti-inflammatory; Lauraceae; Aniba canelilla; DFT; 1-nitro-2-phenylethane; SAR